Terahertz Imaging Simulation Using Silicon-based Microstrip Antenna and Horn Antenna for Breast Cancer Detection - Herry Tony Andhyka; Catur Apriono; Fitri Yuli Zulkifli (Universitas Ahmad Dahlan, 2022)
Breast cancer is one of the most common cancers in the world that cause a lot of mortality. Early cancer detection is crucial to decrease morbidity and mortality rates worldwide. Effective treatment or early intervention is crucial before the disease becomes more incurable. This research contributes to proposing a THz imaging system for early cancer detection, especially breast cancer, by using the benefit of THz radiation. Some approaches are made differently from the previous research, such as the imaging method, the antenna type, and the material for the antenna with the expectation of producing an efficient system and better imaging results. The system consists of one microstrip antenna as a transmitter, 25 horn antenna as a receiver and a breast tissue model. All antenna is designed to meet the requirement specification. The receiver antenna will receive power from the transmitter which will vary due to the absorption of the breast model. The received power will be visualized into a 2D color image. The simulation was able to visualize an image of the breast tissue model. Received power varies from -16.280 dB to -55.241 dB which leads to different color levels to represent the model. Antenna radiation patterns also take a role to cause the phenomenon occurred that leads to differentiation of the breast tissue type. Based on the results, this research has able to simulate a THz imaging system for breast cancer. Further modification to the system can be done to improve the imaging results.